Historical Geospatial Analysis of Tropical Cyclone Intensity and Rainfall Variability in Alor Regency, Indonesia - Thomas Y. Blegur; Khomsin Khomsin (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
Tropical cyclones rarely make landfall in Indonesia; however, their indirect influence can substantially affect regional rainfall variability, particularly in eastern Indonesia. This study aims to analyze the historical geospatial characteristics of tropical cyclone intensity and to quantify their contribution to rainfall variability in Alor Regency, East Nusa Tenggara, over the period 1996–2024. The analysis integrates tropical cyclone best-track data, in-situ daily rainfall observations, and satellite-based rainfall estimates. Geospatial techniques were applied to examine cyclone track density, spatial exposure, and seasonal patterns, while statistical analyses—including descriptive statistics, non-parametric correlation, and linear and non-linear regression—were employed to evaluate temporal variability in maximum wind intensity. The results indicate that tropical cyclone activity in the surrounding region is strongly seasonal, with peak occurrences during the wet season months, while cyclone intensity is dominated by low to moderate categories and exhibits no statistically significant long-term trend. Rainfall analysis reveals that tropical cyclones contribute substantially to monthly rainfall totals, particularly during the early and late phases of the rainy season, when cyclone-related rainfall accounts for a large proportion of climatological monthly rainfall. Spatially, higher rainfall sensitivity is observed in eastern and southern Alor, reflecting the combined effects of moisture advection from nearby seas and local orographic enhancement. These findings demonstrate that tropical cyclones play a critical indirect role in shaping rainfall variability and hydrometeorological risk in Alor Regency, highlighting the importance of incorporating cyclone-related rainfall influences into regional climate assessment, disaster risk reduction, and adaptation planning.